SHARH The Tradition of Commentary in Malay-Jawi Literature - Che' Razi Jusoh (Akademi Jawi Malaysia Sdn Bhd, 2024)
This study is therefore an attempt to investigate the wealth of commentaries that have for centuries nourished the spirit of knowledge among the people of this part of the world. It will serve as an analytical study on the sharḥ of Malay-Jāwī works, in so doing opening up many doors for further study in this area. Plus, it will answer the polemic of whether the sharḥ works in Malay Jāwī literature or even in general, were merely dormant and did not in any way contribute to the growth of knowledge, learning, and culture of Islām and Malay scholarship in particular. Based on the foregoing aims and goals of the study, it is hoped that it will serve as one of the main references for examining and analyzing the significant legacy of our past scholars towards the tradition of knowledge, learning, and scholarship and the production of sharḥ literature in particular, thereby becoming a reference in Malay studies, especially with regard to Malay culture and civilization.